Abnormal High-sensitivity C-reactive Protein is Associated with an Increased Risk of Cardiovascular Disease and Renal Dysfunction among Patients Diagnosed with Type 2 Diabetes Mellitus in Palestine (The Review of Diabetic Studies, 2022)
OBJECTIVE: In this study, we aimed to evaluate the prevalence of high sensitivity C-reactive protein (hsCRP) as an inflammatory mediator and its association with renal function and other biochemical markers in patients with type 2 diabetes mellitus. METHODS: We carried out a cross-sectional study at private healthcare center. We included 453 patients (48.6% males and 51.4% females) with type 2 diabetes mellitus. We obtained sociodemographic, clinical, and laboratory data from patient medical records. We carried out statistical analysis to ascertain associations between parameters. RESULTS: The overall risk of cardiovascular disease (hsCRP > 1 mg/L) among the study participants was 27.2%. Age, gender, body mass index, fasting blood glucose and serum creatinine were significantly associated with risk of cardiovascular disease (hsCRP > 1 mg/L) whereas estimated glomerular filtration rate, vitamin B12, calcium, sodium and metformin users were negatively associated with the hsCRP. CONCLUSIONS: We found a significant positive association of elevated level of C-reactive protein with type 2 diabetes mellitus. Moreover, additional to increased cardiovascular disease risk, hsCRP also seems to be a major inflammatory risk marker indicating renal function loss.